Storage Stability of Minced Chicken Meat and Pork at Ambient Temperature - Rushitha, K; Sudheer, K; Naveen , Z; Chakravarthi , M Kalyana (Journal of Meat Science, 2024)
With the increase in human population, the demand for food has also  risen up. The food processing outlets mostly handle minced meat at  ambient temperatures to cater the consumers choice. Identifying the exact  spoilage time can safeguard the health of the consumer and also minimize  the losses to the food handlers. With this outlook a work was designed in  order to study the spoilage pattern of chicken meat and pork at ambient  temperature. The chicken meat and pork were procured hygienically  from scientifically slaughtered poultry birds and pigs, and then minced  using a mincer with a pore size of 10mm. The minced chicken meat and  pork were analyzed for physico-chemical, microbiological and sensory  parameters at ambient temperature for hourly interval. The results  indicated a significant increase in pH, tyrosine value, TBARS values,  weight loss and microbial profiles (Total plate count, Yeast and mould  count, and Coliform count), and also a significant decrease in ERV and  sensory (appearance, texture, odour and overall acceptability) scores of  both minced chicken meat and pork with increase in storage period.  Hence, it can be concluded that the shelf life of minced chicken meat and  pork at ambient temperature was 3 hours and 6 hours respectively.
Keywords: Ecosystem; Producing; Tissue; Chicken; Temperature.